Deconstructing Informality: A Response to Vulnerability or an Optimal Choice? - Lina Song; Simon Appleton; Zhe Liang (Institute for the Study of Labor (IZA), 2016)
The rapid growth of informal employment in China in recent decades has attracted attention, but to understand its implications, the concept of informality must be deconstructed. We reclassify employment status into three categories: salaried workers who have long-term contracts; the self-employed; and causal workers without long term contracts (working in either the formal or the informal sector). The monthly earnings of the self-employed are much (47%) higher than those casual employees. Self-employment is not necessarily a misfortune and the flexibility it provides may be optimal for some kinds of workers. For example, the self-employed are more likely to be disabled and to have young families. Institutionally, it is still difficult for casual workers and most rural-urban migrant workers to embark on business ownership. Although a large group of rural-urban migrants are employees with longer term contracts, their rural registration (hukou) means they lack the social protection of urban residents. The labour force with rural hukou is more likely to fall into the informal sector and, within that sector, is most likely to be engaged in casual labouring jobs. Policies to support small businesses may be warranted given the detrimental impacts of informality on casual workers. Experimental interventions could be tried along the lines of those used in Peru to provide funds to support entrepreneurial activities by this group to lift themselves out of a poverty trap into more sustainable employment. Skill training, encouragement for innovation, tax credits and reducing institutional constraints on starting up small business should be all considered.
Keywords: J24; J46; J48; 330; informality; vulnerability; self-employment; casual labour; China